2000
DOI: 10.1038/sj.leu.2401777
|View full text |Cite
|
Sign up to set email alerts
|

Identification of variables determining the engraftment potential of human acute myeloid leukemia in the immunodeficient NOD/SCID human chimera model

Abstract: Among a variety of immunodeficient mouse strains the nonobese diabetic (NOD)/LtSz scid/scid strain appears to be most useful in allowing the engraftment of human AML. However, the large variability in ability to engraft and the levels of engraftment reached have not been explained. To address these issues we have investigated the NOD/SCID repopulating ability of 27 newly diagnosed AML samples. Patients were selected for the absence of internal tandem duplications in the Flt3 gene as we previously reported this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 23 publications
6
55
0
1
Order By: Relevance
“…Cells with FAB subtypes M3 and, to a lesser extent, M2, engrafted more poorly than those from other subtypes (Ailles et al, 1999). Rombouts et al reported that a significantly higher engraftment was observed in the FAB class M0 than in FAB classes M2, M4 and M5 (Rombouts et al, 2000b). However, there was also a research reporting that engraftment did not correlate with FAB subtype (Sanchez et al, 2009).…”
Section: Factors Influencing Engraftment Of Human Aml In Immunodeficimentioning
confidence: 98%
See 4 more Smart Citations
“…Cells with FAB subtypes M3 and, to a lesser extent, M2, engrafted more poorly than those from other subtypes (Ailles et al, 1999). Rombouts et al reported that a significantly higher engraftment was observed in the FAB class M0 than in FAB classes M2, M4 and M5 (Rombouts et al, 2000b). However, there was also a research reporting that engraftment did not correlate with FAB subtype (Sanchez et al, 2009).…”
Section: Factors Influencing Engraftment Of Human Aml In Immunodeficimentioning
confidence: 98%
“…Cells from patients with poor prognostic markers (e.g. high WBC, poor risk cytogenetics, FLT3-ITD positive, high CD34 expression) engrafted more efficiently in NOD/SCID mice than general AML cases (Ailles et al, 1999;Kondo et al, 1999;Rombouts et al, 2000a;Rombouts et al, 2000b;Lumkul et al, 2002;Pearce et al, 2006). However, there was a report showed that high WBC and FLT3-ITD were not predictors of engraftment success (Pearce et al, 2006).…”
Section: Scid Modelsmentioning
confidence: 99%
See 3 more Smart Citations